2008
DOI: 10.3155/1047-3289.58.11.1483
|View full text |Cite
|
Sign up to set email alerts
|

Development of North American Emission Inventories for Air Quality Modeling under Climate Change

Abstract: An assessment of how future climate change will impact regional air quality requires projecting emissions many decades into the future in a consistent manner. An approach that integrates the impact of both the current regulations and the longer-term national and global trends is developed to construct an emissions inventory (EI) for North America for the mid-century in support of a regional modeling study of ozone and particulate matter (PM) less than or equal to 2.5 microm (PM2.5). Because the time horizon of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 4 publications
2
14
0
Order By: Relevance
“…43 In the U.S., several studies integrating satellite NO X datasets, ground observational networks, and regional photochemical models to assess NO X emission changes in early 2000 concluded that NO X emissions have been substantially decreased. 44,45 We can speculate this similar trend may be observable in Japan and Korea in the foreseeable future. In Fig.…”
Section: Resultssupporting
confidence: 63%
“…43 In the U.S., several studies integrating satellite NO X datasets, ground observational networks, and regional photochemical models to assess NO X emission changes in early 2000 concluded that NO X emissions have been substantially decreased. 44,45 We can speculate this similar trend may be observable in Japan and Korea in the foreseeable future. In Fig.…”
Section: Resultssupporting
confidence: 63%
“…GISS results utilized are for the Intergovernmental Panel on Climate Change (IPCC) A1B scenario, which is generally viewed as a midrange case that assumes a future world of rapid economic growth with a balance between fossil and nonfossil energy sources (10). Planned controls, e.g., the Clean Air Interstate Rule (CAIR) and others in the United States (11) as well as emission changes in Canada and Mexico (12) (12). Anthropogenic volatile organic compound (VOC) emissions are predicted to decrease about 38%, though total VOC emissions are projected to increase by about 2% as biogenic VOC emissions increase (SI Table S1).…”
Section: Methodsmentioning
confidence: 99%
“…Anthropogenic volatile organic compound (VOC) emissions are predicted to decrease about 38%, though total VOC emissions are projected to increase by about 2% as biogenic VOC emissions increase (SI Table S1). Ammonia (NH3) emissions are predicted to increase by 7% due to growth in human activities (6,12).…”
Section: Methodsmentioning
confidence: 99%
“…The GCAQA is implementing a scenario-based approach to emissions development (Schwartz, 1996), in contrast to approaches in which a single, best guess emission projection is developed (e.g., Woo et al, 2008). The mechanism by which the GCAQA scenarios are translated into future emissions is a critical component of the integrated framework.…”
Section: H Loughlin Et Al: Methodology For Exploring Emission Immentioning
confidence: 99%